Non-classicality of optomechanical devices in experimentally realistic operating regimes - Vacanti, G; Paternostro, M; Palma, G; Kim, MS; Vedral, V (2013)
Enforcing a non-classical behavior in mesoscopic systems is important for the study of the boundaries between quantum and classical world. Recent experiments have shown that optomechanical devices are promising candidates to pursue such investigations. Here we consider two different setups where the indirect coupling between a three-level atom and the movable mirrors of a cavity is achieved. The resulting dynamics is able to conditionally prepare a non-classical state of the mirrors by means of projective measurements operated over a pure state of the atomic system. The non-classical features are persistent against incoherent thermal preparation of the mechanical systems and their dissipative dynamics.